ANALISIS PENDAPATAN USAHATANI DAN PEMASARAN SAYURAN UNGGULAN DI KAWASAN AGROPOLITAN KABUPATEN TANGGAMUS - M Rizky Adityas; Ali Ibrahim Hasyim; Muhammad Irfan Affandi (Lampung University, 2018)
This study aims to analyze the benefits of vegetable farming and preparation of vegetable farming strategy development. The research was conducted in Agropolitan Area of Tanggamus Regency which was chosen purposively. The respondents were 48 farmers and 18 traders. The first objective is analyzed quantitatively using income analysis and R/C. The second objective is analyzed descriptively by using marketing analysis. The results showed that vegetable farming profit in Agropolitan Area of Tanggamus Regency is feasible and profitable with value of R/C > 1. Chili Vegetable is a superior commodity on the income level of farmers. The marketing system of the vegetable in agropolitan region in Tanggamus Dictritc was not efficient since the margin profit ratio in each marketing organization is not even, and the price difference in each marketing organization is too large. Key words : marketing, profit analysis and vegetable farming